Working capital, profitability, liquidity and solvency of healthcare insurance companies - André Luiz de Souza Guimarães; Valcemiro Nossa (BBR: Brazilian Business Review)
The purpose of this study is to analyze the adequacy of a working capital management normative model, in terms of profitability, liquidity and solvency. Through an empirical and analytical research, the analysis of variance results (ANOVA) of a sample containing financial information from 621 healthcare insurance companies for the year 2006 ,show that different working capital structures are associated with different levels of profitability, liquidity and solvency, suggesting a preference order different from the one theorized by Fleuriet / Braga. The results indicate that a certain structure - where financial current assets exceed onerous current liabilities, and cyclical current assets exceed cyclical current liabilities ¿ is associated with higher levels of profitability, liquidity and solvency. In addition, the study reiterates the importance of efficient management of working capital to the performance and survival of healthcare insurance companies.